ALIH KODE DAN CAMPUR KODE DALAM PROSES PEMBELAJARAN PADA MAHASISWA PASCASARJANA PENDIDIKAN BAHASA ARAB UIN MAULANA MALIK IBRAHIM MALANG (Lisanul Arab: Journal of Arabic Learning and Teaching, 2022)
This study was conducted to describe code switching and code mixing in the learning process of postgraduate students of Arabic Language Education (PBA) semester II and the factors that cause code switching and code mixing in the learning process of postgraduate students of Arabic language education in the second semester. Researchers use learning in postgraduate students as the object of research because in learning, language mixing often occurs when delivering material. The method used in this research is a qualitative descriptive method with a conversational engagement listening technique, a conversational engagement free technique and a field note technique or sampling technique. The result of this research is the finding of an external form of code switching, namely code switching from Indonesian to Arabic and code switching from Arabic to Indonesian. As for code mixing found in the study, namely the insertion of words, phrases and clauses. While the factors causing the occurrence of code switching and code mixing were found because of the urgent need of speakers to provide understanding to the interlocutor.